Importance of CXC chemokine receptor 2 in alveolar neutrophil and exudate macrophage recruitment in response to pneumococcal lung infection - Herbold, Wiebke; Maus, Regina; Hahn, Ines; Ding, Nadine; Srivastava, Mrigank; Christman, John W.; Mack, Matthias; Reutershan, Jörg; Briles, David E.; Paton, James C.; Winter, Christine; Welte, Tobias; et al. (Infection and Immunity, 2010)
Sustained neutrophilic infiltration is known to contribute to organ damage, such as acute lung injury. CXC chemokine receptor 2 (CXCR2) is the major receptor regulating inflammatory neutrophil recruitment in acute and chronic inflamed tissues. Whether or not the abundant neutrophil recruitment observed in severe pneumonia is essential for protective immunity against Streptococcus pneumoniae infections is incompletely defined. Here we show that CXCR2 deficiency severely perturbs the recruitment of both neutrophils and exudate macrophages associated with a massive bacterial outgrowth in distal airspaces after infection with S. pneumoniae, resulting in 100% mortality in knockout (KO) mice within 3 days. Moreover, irradiated wild-type mice reconstituted with increasing amounts of CXCR2 KO bone marrow (10, 25, 50, and 75% KO) have correspondingly decreased numbers of both neutrophils and exudate macrophages, which is associated with a stepwise increase in bacterial burden and a reciprocal stepwise decrease in survival in S. pneumoniae-induced pulmonary infection. Finally, application of the CXCR2 antagonist SB-225002 resulted in decreased alveolar neutrophil and exudate macrophage recruitment in mice along with increased lung bacterial loads after infection with S. pneumoniae. Together, these data show that CXC chemokine receptor 2 serves a previously unrecognized nonredundant role in the regulation of both neutrophil and exudate macrophage recruitment to the lung in response to S. pneumoniae infection. In addition, we demonstrate that a threshold level of 10 to 25% of reduced neutrophil recruitment is sufficient to cause increased mortality in mice infected with S. pneumoniae. Copyright © 2010, American Society for Microbiology. All Rights Reserved.
CRIS-Team Scopus Importer:2022-11-17